Superficial Surgical Site Infection in Hand Surgery: A Cross-sectional Study in a Hand Surgery Unit - Bhandari, Prawesh S; Nakarmi, Kiran Kishor; Pudasaini, Pushkar (Journal of Institute of Medicine Nepal, 2023)
Introduction: Superficial surgical site infection (SSI) in hand surgery is generally considered to be less common. Infection of surgical site can lead to poor outcomes. Burden of surgical site infection in hand surgery has not been studied in our part of the world. We sought to determine the prevalence rate superficial surgical site infection in patients undergoing hand surgery in an operation theatre setting. Method: We used standard definition CDC National Healthcare Surveillance Network (NHSN) criteria to evluate 112 consecutive adults undergoing various hand surgery procedures at the end of the second week for superficial SSI. The study was conducted over a period of six month. ( November 2022 to May 2023) Result: The prevalence of superficial surgical site infection was 6.25% . Among those affected 0.02% cases were diagnosed based on signs and symptoms criteria. In 0.03% patient the wound discharge yielded Staphylococcus aureus. The most common cause requiring hand surgery were workplace injuries, household injuries, and injuries due to road traffic accounting for 45.54%, 26.79 %, and 18.75 %, respectively.Crushing type of injury which was the most common of all mechanisms of injury. Conclusion: The prevalence rates of hand procedures are low but not negligible. This under-evaluated condition must be more extensively evaluated in a multicenter study involving larger population.